Analysis Curie Temperature and Hysteresis La0,7Sr0,3MnO3 with Micromagnetic Simulation - Febiantoro, Muhamad Rony; Rohman, Lutfi; Sutisna, Sutisna (Computational And Experimental Research In Materials And Renewable Energy, 2020)
Simulation reseach has been carried out to obtain the characteristic of material La0,7Sr0,3MnO3. The simulation method used atomistic of magnetic materials. Simulations were carried out using Vampire software Micromagnetic simulation were determine Curie temperature and Hysterisis Curve. The monte carlo algorithm was used in this reseach. Simulation were carried out by variation nanocube size 22 nm, 27 nm, and 32 nm. The simulation result show, Curie temperature show in 27 nm have the biggest value and stuck in that value. The characteristics of the Hysterisis curve 32 nm bigger than the others.From the simulation, it is found that the between the temperature and Hysteris curve. More temperature value, the smaller the Hysterisis curve.